2014
DOI: 10.1177/0284185113512123
|View full text |Cite
|
Sign up to set email alerts
|

Venous sac embolization of pulmonary arteriovenous malformation: safety and effectiveness at mid-term follow-up

Abstract: Venous sac embolization for PAVMs might be safe and more effective with no reperfusion than the standard pulmonary arterial embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In this study, we placed some coils inside the venous sac to make a scaffold so as to embolize the feeding artery tightly. It has been reported that embolization of both the feeding artery and venous sac may be useful [ 22 24 ], and some authors recommended tightly packing the venous sac [ 23 ]. However, doing it needs many coils and has a high cost.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we placed some coils inside the venous sac to make a scaffold so as to embolize the feeding artery tightly. It has been reported that embolization of both the feeding artery and venous sac may be useful [ 22 24 ], and some authors recommended tightly packing the venous sac [ 23 ]. However, doing it needs many coils and has a high cost.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Some authors have noted the importance of embolization of feeding artery close to the sac, while others demonstrated the efficacy of venous sac embolization to prevent persistence [ 9 , 11 , 15 17 ]. However, they did not mention where the fistulous point in PAVM is.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing high reperfusion rates and how to decrease them is of clinical importance. Embolization of the feeding artery and the venous sac was previously shown to prevent reperfusion (1,19), and our primary embolization was performed according to this method in the present study. However, the reperfusion rates of primary embolization were higher; the 3-month, 6-month, 12-month, and 24-month reperfusion rates for the 12 primary embolization procedures were 8%, 27%, 36%, and 49%, respectively.…”
Section: Discussionmentioning
confidence: 93%